Enhanced optical and electrical performance of Ge1−xSnx/Ge/Si(100) (x = 0.062) semiconductor via inductively coupled H2 plasma treatments. (20th March 2019) - Wang, Buguo; Hogsed, Michael R; Harris, Thomas R; Wallace, Patrick M; Kouvetakis, John
Abstract: The structural, electrical and optical properties of a unintentionally doped Ge1− x Sn x ( x = 6.2%) alloy semiconductor both as-grown and after a hydrogen plasma treatment or 'hydrogen passivation' are investigated by high resolution x-ray diffraction, atomic force microscopy, and temperature-dependent Hall-effect and photoluminescence (PL) measurements. The samples were grown via reactions of SnD4 and Ge3 H8 on Ge buffered Si wafers at 305 °C and subsequently subjected to a hydrogen plasma environment generated using an inductively coupled H2 approach (ICP). The plasma treatments showed no appreciable change in the structural, compositional and morphological properties of the samples indicating no measurable degradation of the materials quality has occurred. However, the H passivation significantly alters the electrical activity of as-grown defects and impurities in the epilayer, resulting in electrical conductivity of passivated sample that is more than 2 times higher at 300 K and 30 times higher at 10 K. The as-grown samples showed conduction-type changes with temperature (manifested by singularities in the apparent carrier concentrations around 14 and 255 K), while the background n-type carrier concentration of the hydrogen treated analogs varied smoothly with temperature. In particular at 300 K, the carrier concentration was reduced from the background 4.61 × 10 17 cm −3 in the as-grown material to 5.68 × 10 16 cm −3 in the H treated counterpart due to potential passivation of deleterious point defects, a highly desirable outcome for effective device performance. The room temperature PL intensity increased ∼5 times (more than 3 times at 5 K) upon hydrogen treatment due to electrical passivation of deep acceptor states. Hydrogen plasma treatments are thus found to enhance the electrical and optical responses of the samples, suggesting that conventional ICP treatments could be used as a processing step to improve the properties of newly developed Sn-based group IV semiconductors using straightforward and relatively low temperature protocols.